2022
DOI: 10.1128/spectrum.03392-22
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Features of Mycobacterium avium subsp. paratuberculosis Strains Circulating in the West of France Deciphered by Whole-Genome Sequencing

Abstract: Mycobacterium avium subsp. paratuberculosis causes Johne's disease in ruminants, which is present worldwide and has significant negative impacts on the dairy cattle industry and animal welfare. Prevention and control of M. avium subsp. paratuberculosis infection are hampered by knowledge gaps in strain virulence, genotype distribution, and transmission dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…paratuberculosis (MAP) is a microorganism characterised by an extremely slow growth rate both in a controlled environment ( in vitro ) and within living organisms ( in vivo ). One of the consequences of this slow pace is a low mutation rate and the extremely well-conserved and closed core genome ( 14 , 15 , 17 , 20 ). In the field of MAP epidemiology, traditional population genetic and diversity analysis methods such as VNTR or SSR analysis have currently been largely supplanted by WGS approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…paratuberculosis (MAP) is a microorganism characterised by an extremely slow growth rate both in a controlled environment ( in vitro ) and within living organisms ( in vivo ). One of the consequences of this slow pace is a low mutation rate and the extremely well-conserved and closed core genome ( 14 , 15 , 17 , 20 ). In the field of MAP epidemiology, traditional population genetic and diversity analysis methods such as VNTR or SSR analysis have currently been largely supplanted by WGS approaches.…”
Section: Discussionmentioning
confidence: 99%
“…While the de novo method circumvents biases related to indels or genetic translocations, the less computationally intensive reference genome alignment is appropriated for reconstructing and comparing core genomes. Consequently, building epidemiological trees based on SNP analyses of the core genome remains the predominant approach in evaluating potential epidemiological links within the MAP field, due to its notably low mutation rate ( 14 , 17 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, intra-herd variability was observed in four out of 11 herds, of which multiple samples per farm were analyzed. Another recent study analyzing MAP by WGS showed that MIRU-VNTR typing lacks resolution for fine tracing of MAP strain circulation between and within herds ( 15 ). Despite these limitations, MIRU-VNTR typing, in combination with the differentiation between C-type and S-type MAP including subtype identification, can disclose an interesting insight about the strain variability in view of a temporal or geographical distribution of INMV types and the proportions of C- and S-type MAP strains.…”
Section: Discussionmentioning
confidence: 99%
“…Various molecular techniques have been used for investigating genetic diversity among MAP, such as restriction fragment length polymorphism (10), short-sequence repeat and pulsed-field gel electrophoresis typing (11), mycobacterial interspersed repetitive unit and variable-number tandem repeat (MIRU-VNTR) (12) or single nucleotide polymorphism (SNP)-based assay (13). For an ultimate resolution of the phylogenetic relationships between strains, whole-genome sequencing (WGS) of isolates can be used (9,(14)(15)(16), however requiring cultured isolates, which are laborious and time-consuming to obtain. Bovine paratuberculosis is caused mostly by C-type MAP and only in a few cases by S-type strains of MAP (1).…”
Section: Introductionmentioning
confidence: 99%
“…These include the 8 locus Mycobacterial Interspersed Repetitive Unit-Variable Number Tandem Repeat (MIRU-VNTR) and the 11 locus SSR typing methods, both of which are commonly used in epidemiology and source tracking studies ( 24 , 25 ). More recently, whole-genome sequencing (WGS) followed by single-nucleotide polymorphism (SNP) analysis has allowed for strain typing at a much higher resolution than previously possible, leading to the deciphering of new information ( 23 , 26 28 ).…”
Section: Introductionmentioning
confidence: 99%